New records of philometrids (Nematoda: Philometridae) from marine fishes off Japan, including description of Philometra kidakoi sp. n. and Congerinema japonicum gen. et sp. n - Moravec, Frantisek; Nagasawa, Kazuya; Nitta, Masato; Tawa, Atsushi (Folia parasitologica, 2019)
Occasional examinations of some marine fishes in Japan revealed, in addition to other parasites, the following eight species of philometrid nematodes (Philometridae) (all females only): Philometra kidakoi sp. n. from the ovary of Gymnothorax kidako (Temminck et Schlegel) (Muraenidae); Philometra pinnicola (Yamaguti, 1935) from the operculum of Epinephelus akaara (Temminck et Schlegel) (Serranidae); Philometra sebastisci Yamaguti, 1941 from the ovary of Sebastes cheni Barsukov (Scorpaenidae) (new host); Philometra madai Quiazon, Yoshinaga et Ogawa, 2008 from the ovary of Acanthopagrus schlegelii (Bleeker) (Sparidae) (new host); Philometra isaki Quiazon, Yoshinaga et Ogawa, 2008 from the ovary of Parapristipoma trilineatum (Thunberg) (Haemulidae); Philometra sp. from the ovary of Synanceia verrucosa Bloch et Schneider (Synanceiidae); Congerinema japonicum gen. et sp. n. from the subcutaneous tissue of Conger myriaster (Brevoort) (Congridae); and Clavinema mariae (Layman, 1930) from the operculum of Acentrogobius pflaumii (Bleeker) (Gobiidae). Specimens of all species are described based on light and scanning electron microscopical examinations. Philometra kidakoi sp. n. is the first gonad-infecting philometrid from the Muraenidae. The new monotypic genus Congerinema gen. n. is characterised by the unique net-like cuticular ornamentation on the female body. Clavinema mariae is considered to be a complex of several cryptic species and a need of the discovery of conspecific males is stressed (this also concerns other philometrid species with unknown males). At present, the fauna of philometrid nematodes parasitising marine fishes in Japanese waters is represented by 22 nominal species belonging to four genera.
Keywords: Microscopy, Electron, Scanning; Spirurida Infections; Dracunculoidea; mikroskopie elektronová rastrovací; new taxa; infekce hlísticemi řádu Spirurida; East Asia; mužské pohlaví; Japanese seas; Japonsko; ženské pohlaví; Microscopy; zvířata; nemoci ryb; Host-Parasite Interactions; Scorpaeniformes; Japan; Species Specificity; Anguilliformes; Philometra; interakce hostitele a parazita; Fish Diseases; Fishes; Perciformes; druhová specificita; ryby; Female; mikroskopie; Male; Animals